Organizational partnerships for food Policy research impact: A review of what works - Mabiso, Athur; van Rheenen, Teunis; Ferguson, Jenna (International Food Policy Research Institute, 2013)
This paper contributes to our understanding of food policy–research partnerships and provides a review of the theory and empirical literature about the factors that contribute to effective food policy–research partnerships. The literature points to the emergence of organizational partnerships as primarily driven by subjective perceptions about potential partners, the complex and uncertain external environment, access to resources through partnership and expectations of potential impact of the partnership.